Testing Listening by Using Audio Aid and Animated Film - Dian Fajrina; Syamsul Bahri; Mohammad Kholid (Proceedings of AICS - Social Sciences, 2016)
This study is a field research which is descriptive quantitative in nature. The purpose was to find out whether there are any differences in listening achievement between listening to audio aid and listening as well as watching to an animated film. The participants were 20 semester six students of English Education Syiah Kuala University. The instruments used in this study were two sets of test, one by listening to audio aid, and the other by listening and watching animated film. The result of the tests showed that the mean score of the animated film test was higher than the audio aid test. It was proven by t-score result where the t-score was 11.5, referred to the t-table at level of significance 5% with the degree of freedom (df) was 19. The result of t-score was higher than the t-table. In conclusion, the alternative hypothesis, which states that there is a different result on listening achievement between listening to audio aid and listening as well as watching animated film, is accepted. Therefore, it is suggested to the English teachers to use animated film as a media in teaching Listening Comprehension.